In vivo hepatic reprogramming of myofibroblasts with AAV vectors as a therapeutic strategy for liver fibrosis - Rezvani, Milad; Wiedtke, Ellen (Cell stem cell, 2016)
Liver fibrosis, a form of scarring, gradually develops in chronic liver diseases when hepatocyte regeneration cannot compensate for hepatocyte death. At earlier stages, collagen produced by activated myofibroblasts (MFs) functions to maintain tissue integrity, but upon repeated injury, collagen accumulation suppresses hepatocyte regeneration, ultimately leading to liver failure. As a strategy to generate new hepatocytes and limit collagen deposition in the chronically injured liver, we developed in vivo reprogramming of MFs into hepatocytes using adeno-associated virus (AAV) vectors expressing hepatic transcription factors. We first identified the AAV6 subtype as effective in transducing MFs in mouse models of chronic liver disease. We then use lineage-tracing approaches to show that hepatocytes reprogrammed from MFs replicate primary hepatocyte function, and that liver fibrosis in AAV treated animals is reduced. Because AAV vectors are already used for liver-directed human gene therapy, our strategy has potential for clinical translation into a therapy for liver fibrosis.
Gesehen am 31.01.2019